Designing TALARIA: a New Software to Support Resource Sharing of International Communities - Silvana Mangiaracina (5225537) (2023)
This paper was given by Silvana Mangiaracina, Alessandro Tugnoli, Debora Mazza, and Rabih Kahaleh,  Dario Nobili Library, Bologna Research Area, National Research Council, Bologna, Italy   In 2020, the COVID-19 situation forced academic libraries to move exclusively to the Web. To  respond to the COVID emergency, in April 2020 a group of librarians under the aegis of IFLA  created “Resource Sharing during COVID-19” (RSCVD): the first experiment in free digital resource sharing worldwide. RSCVD is based on the voluntary contribution of hundreds of librarians around the world, who  worked with the tools available at that moment in order to share documents held in their libraries  with the world academic community. After the success of this initiative in the face of the COVID  emergency, the Erasmus Plus Programme, through the HERMES project, gives us the opportunity to  design a new Resource Sharing software platform for the RSCVD international community. TALARIA software is being designed to support library communities in their resource sharing (RS)  management. We aim to build a flexible platform to support different needs and policies of a RS  community. Librarians will have access to the RSCVD international community when they have to  locate very difficult resources, those RS requests that they are not able to find in their usual  1 collaboration network. For this reason, TALARIA supports the management of difficult requests,  allowing users to send a request to all libraries in the community, as well as to a specific library. The software will also support interoperability with other RS management systems, based on the ISO 18626 protocol, in order to connect existing national resource sharing networks. TALARIA will be  released as Open Source software, and it will use free Open Source third party software and external  services as much as possible. In this paper we present the state of the art of the project and the new concepts introduced in  TALARIA that may contribute to shaping a different and more effective way of resource sharing  among libraries world-wide.